2017
DOI: 10.1590/1980-5497201700020001
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and low birth weight in an industrialized city in Southeastern Brazil, 2003-2006

Abstract: Introduction: Birth weight is an important indicator of several conditions that manifest earlier (as fetal and neonatal mortality and morbidity, inhibited growth and cognitive development) and later in life such as chronic diseases. Air pollution has been associated with adverse pregnancy outcomes. Objective: Retrospective cohort study investigated the association between low birth weight (LBW) and maternal exposure to air pollutants in Volta Redonda city, Rio de Janeiro, Brazil, from 2003 to 2006. Methods: Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
5
0
6
Order By: Relevance
“…Open access road traffic air pollution during pregnancy and birth weight. Reis et al 9 found that exposure to PM 10 and O 3 in the second and third trimesters of pregnancy may lead to low birth weight (LBW), with a dose-response relationship. Agay-Shay et al 10 found that greening in residential areas has the strongest correlation with birth weight and LBW, which is consistent with the results of Laurent et al 11 Besides perinatal exposures, the effects of genetic factors and current living-related environmental exposures on children's growth and development have also been the focus of maternal and child health in recent years.…”
Section: Strengths and Limitations Of This Study ► The Main Strength mentioning
confidence: 99%
“…Open access road traffic air pollution during pregnancy and birth weight. Reis et al 9 found that exposure to PM 10 and O 3 in the second and third trimesters of pregnancy may lead to low birth weight (LBW), with a dose-response relationship. Agay-Shay et al 10 found that greening in residential areas has the strongest correlation with birth weight and LBW, which is consistent with the results of Laurent et al 11 Besides perinatal exposures, the effects of genetic factors and current living-related environmental exposures on children's growth and development have also been the focus of maternal and child health in recent years.…”
Section: Strengths and Limitations Of This Study ► The Main Strength mentioning
confidence: 99%
“…Diversos estudos apresentam resultados dos efeitos da poluição do ar na saúde da população (BARI et al, 2018;CIARELLI et al, 2016;FREITAS et al, 2016;KARAGULIAN et al, 2015;REIS et al, 2017;RIZKY et al, 2016;RODRIGUES et al, 2017;VARDAR et al, 2014), sendo também relacionados às cidades com elevado número de pessoas (GUZMÁN et al, 2017). Devido ao seu diâmetro micrométrico, o MP pode rápida e facilmente seja inalado (IPCC, 2014) e, segundo Braga et al (2001), a partícula pode adsorver alguns gases em sua superfície, podendo também ser transportados até o sistema respiratório.…”
Section: Introductionunclassified
“…A exposição aos poluentes atmosféricos aponta para aumento no número de internações devido a agravos no sistema respiratório e cardiovascular com desfechos em lesões pulmonares e infarto, adversidades durante a gravidez, como prematuridade, restrição do crescimento e baixo peso ao nascer, e mortalidade quando existem complicações (RODRIGUES et al, 2017;FREITAS et al, 2016;REIS et al, 2017;RIZKY et al, 2016). Os efeitos na saúde variam conforme a composição química, período de exposição e concentração dos poluentes atmosféricos (ALVES et al, 2015).…”
Section: Introductionunclassified
“…Em relação à análise da expressão gênica não foi observado diferenças significativas para os genes GABA-A-Rα2 (P=0,067), 5-HT1A (P=0,405) e HO-1 (Stieb et al, 2012;Li et al, 2017;Reis et al, 2017). Outros estudos conduzidos em nosso laboratório relataram que a exposição à poluição da cidade de São Paulo provocou baixo peso ao nascer em camundongos cujas mães foram expostas a poluição durante o período gestacional (Veras et al, 2008;Veras et al, 2009).…”
Section: Expressão Gênicaunclassified